Intrathecal Trastuzumab as a Novel Simplified Therapeutic Strategy for Isolated Metastases in the Leptomeninges in HER2-Positive Breast Cancer: A Case Report and Review of Literature - Lokesh K. Nagendrappa; Ananda N. Shankaranarayana; Beulah E. Koshy; Suresh Babu; Rudresha A. H.; Rajeev L. Krishnappa; Smitha Saldanha; Ajinkya D. Pophale (Indian Journal of Medical and Paediatric Oncology)
Leptomeningeal metastases is one of the dreaded complications of metastatic breast cancer, which has a very poor prognosis despite standard treatment, which includes systemic chemotherapy, targeted therapy, and radiation therapy. Intrathecal (IT) therapy has also been used in various studies, which includes IT methotrexate and IT trastuzumab (if the cancer is found to be HER2 + ).